2012
DOI: 10.20882/adicciones.98
|View full text |Cite
|
Sign up to set email alerts
|

Recaídas en la adicción a cocaína: una revisión

Abstract: . Many and varied factors and variables identified with some predictive power were identified, notably psychosocial problems, negative emotional states, anxiety, self-efficacy, psychopathological comorbidity, addictive severity, and several variables related to the treatment process. Knowledge about the relapse process has increased considerably in recent years, but although the influence of certain factors on relapse in cocaine use now seems clear, specific research is still s carce and inconclusive.Key words… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 46 publications
0
2
0
4
Order By: Relevance
“…2017;39 (4) Crack-cocaine use and family cohesion suggest that an unstructured family environment is a risk factor for relapse in SUD and is associated with a greater severity of dependence. 14 The establishment of healthy emotional bonds between parents and children, for example, based on responsibilities, limits, support and affection, is a protective factor against drug use. 9 The present study showed that crack-cocaine users have poorer family functioning in relation to personal commitment and have weaker family ties than do alcohol-only users, which may contribute to low family cohesion and the choice of hard drugs, such as crack cocaine.…”
mentioning
confidence: 99%
“…2017;39 (4) Crack-cocaine use and family cohesion suggest that an unstructured family environment is a risk factor for relapse in SUD and is associated with a greater severity of dependence. 14 The establishment of healthy emotional bonds between parents and children, for example, based on responsibilities, limits, support and affection, is a protective factor against drug use. 9 The present study showed that crack-cocaine users have poorer family functioning in relation to personal commitment and have weaker family ties than do alcohol-only users, which may contribute to low family cohesion and the choice of hard drugs, such as crack cocaine.…”
mentioning
confidence: 99%
“…Esta cualidad consiste en la creencia en sus propias capacidades para lograr metas planteadas. Al momento de evaluar la autoeficacia del paciente es importante indagar en los sentimientos, ideas, historias de vida, tiempo de consumo y tiempo abstinencia (si lo tuvo)hasta su recaída (Sánchez-Hervás & Llorente del Pozo, 2012).…”
Section: Introductionunclassified
“…En este sentido, se ha encontrado evidencia que revela una relación entre la impulsividad y la afectividad negativa en el retorno al consumo, así como entre variables psicosociales, factores emocionales negativos, autoeficacia y funcionamiento familiar como elementos asociados al proceso de recaída mientras que el estrés, apoyo social y autoestima serían variables intervinientes en la adhesión al tratamiento [8][9][10][11] .…”
Section: Introductionunclassified
“…Así pues, considerando el carácter multicausal de la conducta 10 , y basándose en resultados de investigaciones previas, se planteó el siguiente modelo como hipótesis de investigación (figura 1):…”
Section: Introductionunclassified